Targeted therapies in advanced differentiated thyroid cancer. Issue 8 (September 2015) - Carneiro, Raquel M.; Carneiro, Benedito A.; Agulnik, Mark; Kopp, Peter A.; Giles, Francis J.
Highlights Sorafenib and lenvatinib are approved for advanced differentiated thyroid cancer. MAPK and PI3K/AKT/mTOR pathways play a central role in differentiated thyroid cancer. Combination of BRAF and MEK inhibitors is being investigated in thyroid cancer. The TCGA characterized papillary thyroid cancer into BRAF- and RAS-driven tumors. Redifferentiation agents have an important potential for thyroid cancer treatment.